The Role Of Islamic Movements In Enhancing Dakwah Work: The Malaysian Experience - Badlihisham Mohd Nasir; Norhidayu Muhamad Zain; Ahmad Syukran Baharuddin (Universiti Sains Malaysia, 2024)
KEMANUSIAAN Vol. 26, Supp. 1, (2019), 131–149